Hubungan Pelaksanaan Manajemen Patient Safety dengan Mutu Pelayanan Kesehatan di Ruangan Rawat Inap Rumah Sakit Madina Bukittinggi - Miftahul Khairani; Pratiwi Soni Redha; Sylvia Adi Putri (Universitas Mercubaktijaya, 2025)
Patient safety can try to prevent injuries due to errors caused by doing or not doing an action that should be taken. This can be achieved by improving the quality of health services provided by all hospital staff. The purpose of this study was to determine the Relationship between the Implementation of Patient Safety Management and the Quality of Health Services in the Inpatient Room of Madina General Hospital Bukittinggi. This study used a quantitative correlation method. This data collection was carried out in August 2024 by giving questionnaires to 25 inpatient nurses. The results of this study showed that there were 5 people (71.4%) who had the category of poor patient safety and poor health service quality, while poor patient safety with good service quality were 3 people (16.7%), good patient safety with poor service quality were 2 people (28.6%), then good patient safety with good service quality were 15 people (83.3%). The results of the statistical test obtained a value of p = 0.017 (p <0.05) meaning that the implementation of patient safety management is related to the quality of health services so that the better the implementation of patient safety, the higher the quality of health services in the inpatient room of Madina Bukittinggi General Hospital. Suggestions in this study are expected for further researchers to be able to perfect this study.